Combating piracy and armed robbery against ships: international cooperation in high risk areas - Ahmed, Kyaw Hla Win @ Md Hassan; Hamid, Abdul Ghafur@Khin Maung Sein; Ali Mohamed, Ashgar Ali (LexisNexis, 2016)

(untitled)
Incidents of piracy and armed robbery against ships have sharply increased in the last decade of the 20th Century and the early 21st Century. The high rate of such incidences occur due to states which suffer from political uncertainty or lack of effective enforcement power in their respective maritime jurisdictions. The situation in Somalia reflects this notion in full account. There would be no hope to expect such a state to conduct efficient surface and aerial patrols in its maritime jurisdiction on its own. Therefore, prevention and suppression of such maritime crimes in high risk areas should be conducted by the international community as a whole. Accordingly, this paper intends to search for a viable way in which the international community can cooperate without impairing the sovereignty of the respective states in high risk areas. It is suggested that an international naval and air force should be established under the UN Security Council to operate surface and aerial patrols in high risk areas all over the world. This exercise should be done in cooperation with the regional powers in the respective state and cease when it is capable of conducting efficient surface and aerial patrols on its own or jointly with other states.